PENILAIAN KEBERHASILAN REKLMASI LAHAN BEKAS TAMBANG PADA BLOK AREA PARINGIN HIGH WALL 2 PT ADARO INDONESIA KALIMANTAN SELATAN - Ratna Sari; Yulius G. Pangkung (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
The consequences of a mining operation can be both positif and negatif impacts. The negative impact of mining occurs in the terms of environmental damage. To repair the damage that has an impact on the environment, reclamtion activities are carried out. PT Adaro Indonesia is a company engaged in coal mining by implementing open pit mining using the Strip Mine method, one of which is located in the Paringin High Wall 2 area block, Balangan Regency, South Kalimantan Province. Evaluating the activities carried out in the ex-mining land reclamation process is necessary in order to determine the success rate of reclamation by providing an assessment of each reclamation activity that has been carried out based on the Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia No. 26 of 2018 Annex VI No. 1872 K/30/MEM/2018, concerning Guuidelines for the Implementation of Reclamtion and post-mining and post-operations in Mineral and Coal Mining Business Activities. The results of the evaluation of the success rate of reclamation at PT Adaro Indonesia in 2019 in the Paringin High Wall 2 area block was 92% with an area of 37.95 ha was categorised as ‘good’, but there are several parameters that have been carrid out but have not been maximized